Globalization and state transformation in China - Zheng, Yongnian (Cambridge Asia-Pacific studies., 2004)
Zheng explores how China's leaders have embraced globalization and market-oriented modernization. While they have been open to Western ideas in rebuilding the economic system, they have been reluctant to import Western concepts of democracy. The author argues that this selectivity will impede China's progress in becoming a modern nation state.